Kepemimpinan Kepala Sekolah dalam Mengelola Sekolah Efektif - Asep Muljawan (STAI Asy-Syukriyyah, 2018)
Leadership is ability, skills, guidance, motivate, supervise to influence the behavior of human as the goal. Although the leadership of principal related to the competency including hard skill or soft skill to give the affect human resources in order to achieve its objective and targets set. The effective school has good management standards, transparent, responsible and accountable, empowers as important component including internal and external factor as achieve the vision – mission – goals of the school effectively and efficiently. The leadership of the principal will give the strong affect to get effectively of school. Because it was related to the figure of principal in order to achieve the vision – mission – goals of the school.